Elevação do nível do mar no município de Vitória-ES : vulnerabilidades, impactos e possíveis ações de resposta - Nali, Jôze Oliveira (2011)
One of the most important consequences of climate change, especially for coastal cities, is the elevation of sea-level rise (SLR) which will cause enormous need for adaptation and reorganization of urban space. In order to discuss the potential impacts of floods will cause the elevation on the population and on five elements that make up the urban infrastructure of Vitória-ES (drainage system, sewer system, road system, coastal protection works and buildings utilities) a diagnosis of areas of the city are flooded by the current sea level, and predictions based on scenarios of rising SLR 0,40m, 0,60m and 1,50m, based on the average high tide. For each impact analysis have been proposed response actions have been grouped into three categories: adaptation, protection and retreat. The results showed that most of the population and the five elements of urban infrastructure are located in areas considered at risk, and the most vulnerable areas coincide with the regions occupied by the system and mangrove areas that were grounded in the past. Because the specifics of each site was not possible to define a unique solution, therefore, the proposed actions should be carefully studied and planned. The proposed methodology allowed us to determine areas susceptible to flooding caused by the action of the sea current and future and can be applied in other coastal regions with characteristics similar to Vitória, since, have altimetric data in appropriate scale and that the information is to be evaluated mapped.